RISK FACTORS FOR THE OCCURRENCE OF BURNOUT SYNDROME AMONG NURSES IN SECONDARY HEALTH CARE: / - Bogdanović Vasić, Slobodanka; Mićić, Milija; Savić, Nikola; Arandjelović, Branimirka; Joković, Dragan; Pavlović Jugović, Katarina; Andjelić, Sladjana (Halo 194 Scientific Journal of Emergency Medicine, 2023)
SUMMARYIntroduction The burnout syndrome of nurses occurs when the intensity of the stressor exceeds the realistic capabilities of the individual/worker. Methods The research was conducted as a cross-sectional study, the sample consisted of 58 nurses/technicians. As a research instrument, a questionnaire specially constructed for this study was used, which incorporated 14 questions related to the assessment of burnout syndrome. Results Descriptive statistics methods were used in the analysis of the obtained results. The largest number of respondents (66%) primarily recognized stress at the workplace compared to other studied stressors; 69% of the sample feel overloaded at work, and 27% feel constant fatigue regardless of the amount of sleep and rest. By assessing the existence of burnout syndrome, which was carried out on the basis of a point system and the original scale (based on the semantic differential scale), it was determined that 4% of respondents were professionally burned out, 15% were affected by burnout syndrome, that 32% were at risk, and that 40 % of the sample is a candidate for its origin. Conclusion Nurses/technicians are continuously exposed to stress in the workplace due to the very nature of the work they perform. Therefore, the activities of all reference bodies and institutions should be focused on designing preventive strategies related to burnout at work.
Keywords: stress; burnout syndrome; risk factors; nurses; hospital